De gordas a plus size: mudanças na representação das mulheres consideradas acima do peso - Marcelja, Karen Grujicic (2018)
For centuries, discourses about beauty have involved the female body in delicate power relations, in addition to transforming it into the object of consumption and desire in different societies. In the last decades, the body has gained even more importance with the possibility of aesthetic and surgical interventions for beauty and physical performance. For all this, the figure of the fat, the potbellied and the sedentary became an indication of failure before so many possibilities of beauty, health and success released by advertising and the media and general. However, since the early 2000s something has been changing in this discourse. Blogs, social networks and other alternative media have been releasing a more optimistic message about obesity. Without apologies to fat, Internet encourages self-love and the end of suffering caused by useless diets and treatments to lose weight. These channels are lead by young women who are supposed to have learned to like themselves and to overcome issues such as prejudice, lack of accessibility and representativeness. Some bloggers already add up to hundreds of thousands of followers and have achieved good advertising contracts thanks to their power of influence on social networks. A good part of this positive discourse is fashion, which already sees in people considered to be overweight an important lode for business. The so-called fashion plus size, as the segment was named, today moves the fashion industry more than any other, and already has events, parades, stylists and own models, all increasingly sought after. Even in the face of this new scenario in relation to obesity, is it possible to imagine that the changes have come to stay? This paper discusses a bit of the history of the fat body and the building of beauty standards, as well as the paradigms that social networks and mass culture are helping to break down by proposing the notion that it is possible to have extra kilos and be beautiful and, above all, happy